Epic lessons : an introduction to ancient didactic poetry - Toohey, Peter, 1951- (London : Routledge, 1996)
Didactic Epic was enormously popular in the ancient world. It was used to teach Greeks and Romans technical and scientific subjects, but in verse. Epic Lessons shows how this scientific poetry was intended not just to instruct but also to entertain.
1. Who reads didactic epic? -- 2. Word of mouth: Orality and didactit poetry from Hesiod to Emedocles -- 3. The Universe as a book: Hellenistic literacy and the poems of Aratus and Nicander -- 4. Roman renewal: Cicero and Lucretius -- 5. Politics, power, and play: polyphony in Virgil's Georgics and Ovid's Fasti -- 6. Amusements for a smoky december: Horace on poetry and Ovid on Eros -- 7. Humans, nature, and god: epic lessons in the first century -- 8. Resisting instinct: hunting, fishing, science, and god -- 9. Didactic dinners: instruction in narrative epic and in the novel -- 10. A literary history of leisure? The didactic epic
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: řecká antická poezie; latinská starověká poezie; epická poezie -- starověké Řecko; epická poezie -- starověký Řím; didaktická poezie -- starověké Řecko; didaktická poezie -- starověký Řím; literatura a věda -- starověké Řecko; literatura a věda -- starověký Řím; literárněvědné rozbory; Greek ancient poetry; ancient Latin poetry; epic poetry -- ancient Greece; epic poetry -- ancient Rome; didactic poetry -- ancient Greece; didactic poetry -- ancient Rome; literature and science -- ancient Greece; literature and science -- ancient Rome; literary criticism and history; monografie; e-knihy online; monographs; e-books online